Scabies and nocturnal pruritus: preliminary observations in a group of African migrants - Stefano Veraldi; Rossana Schianchi; Gianluca Nazzaro (Journal of Infection in Developing Countries)
Introduction: Pruritus of scabies is due to a type IV T cell-mediated reaction to the mite’s saliva, eggs, excrements and other products released by the mite during its life cycle. Movements of the mite also induce pruritus. According to the literature, scabies pruritus has higher frequency and intensity at night.